La Mora Debitoria En Los Contratos Y Su Incidencia Jurídica Para Las Partes Del Proceso Civil Según Las Sentencias Emitidas En Los Juzgados De Lo Civil Y Mercantil Del Cantón Riobamba En Los Años 2012 Y 2013 - Reino Quishpe, José Gabriel (2015)
The present research, is comprised of four chapters, distributed as follows. Chapter I is the guicling framework, which comprise the objectives for which the research was conducted, aimed at determining how the blackberry debitoria contracts !egally affects the parties to the civil process accordinq to the judqmenls in courts of Civil and Cornmercial Riobamba Canton; likewise discussed the rationale that visibly identifies the legal and legal reasoning that had the investigator to d ecide to c onduct this research. In Chapter 11 has developed the the oretical fr ame work in which the theoretical fou n d ation of the research is included; ie an analysis of legal and doctrinal nature of contracts, classification, vices and el ements that carry its reali zation as well as a detailed and thorcugh study of the debitoria mora is done by analyzing its cau ses and ty p e s, and finelly the le g al in cidence in p a rts of the civil process encompassing economic and legal consequences of defa ult by the debt or. L ater, in Cha pter 111 has been carrlsd out iield research, to gether with the metho d ology applied in the develo p m ent of this research, considering the sub stantial inf orm ation provided by the Cou rts of Civil and Mercantile Chimboraz o, with in order to properiy inform research, as well as to the fulfillment of the objectives. Fi n ally, in Cha pter IV concl usi o ns and recommendation_s on the most siqnificant and rele vant to thls work le gal research as pect are noted.